Evaluación de dos polimeros adherentes en el recubrimiento órgano-mineral de urea, Latacunga – Cotopaxi, 2020 – 2021” - Córdova Salazar, Yomara Katherine (2021)
This research was carried out at the Agronomy Laboratory of the Technical University of Cotopaxi, Eloy Alfaro parish, Canton Latacunga, Province of Cotopaxi, with the objective of evaluating the behavior of two adherent polymers and their effect on the physical characteristics of organ coatings. -minerals in urea. A complete random design was applied with a factorial arrangement of 2 x 4 + 1, giving a total of 9 treatments and 27 experimental units. The organic materials used were cow manure, humus, minerals zeolite, phosphate rock, Ethocel polymers and potato starch. The characteristics that were evaluated were: hardness, buoyancy, volume and amount of water absorption of coated urea. The following results were obtained: T6 (Ethocel + humus + zeolite + urea) is the one that obtained the highest average with 60.42 kg / cm2 for hardness). In the buoyancy variable, treatment T7 (Ethocel + cow manure + phosphoric rock + urea) presented the average with 0.04 m / s, in the variables volume and amount of water absorption of the coated urea despite the fact that it does not have significant difference there is a numerical difference, since they have in common the ethocel polymer, cow manure and phosphate rock. In the economic analysis, the treatment with the lowest cost in its preparation was treatment T2 (potato starch + humus + zeolite + urea) with $ 2.72 per kilogram. It is concluded that the T7 treatment (Ethocel + cow manure + phosphate rock + urea) was identified as the most efficient treatment for the organo-mineral coating, due to the characteristics of ethocel, which is a water-insoluble and organosoluble polymer, which forms a film for extended release, Zeolite allows it to be lighter and phosphate rock has slow solubility.